Look, no wires! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The potential of wireless technology is exciting a lot of interest these days. 'Think Wireless A virtual miracle has appeared in the form of the handheld mobile cellular phone, and low-cost satellite links' we wrote in Spore 92 (see: 'I connect,...